1987
DOI: 10.1172/jci113064
|View full text |Cite
|
Sign up to set email alerts
|

Altered kinetic properties of the branched-chain alpha-keto acid dehydrogenase complex due to mutation of the beta-subunit of the branched-chain alpha-keto acid decarboxylase (E1) component in lymphoblastoid cells derived from patients with maple syrup urine disease.

Abstract: Branched-chain ac-keto acid dehydrogense (BCKDH) complexes of lymphoblastoid cell lines derived from patients with classical maple syrup urine disease (MSUD) phenotypes were studied in terms of their catalytic functions and analyzed by immunoblotting, using affinity purified anti-bovine BCKDH antibody. Kinetic studies on three cell lines derived from patients with the classical phenotype showed sigmoidal or near sigmoidal kinetics for overall BCKDH activity and a deficiency of the El component activity.An immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

1988
1988
2005
2005

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…The Vm. and apparent Km values were [13][14][15] nmol/h per milligram ofprotein and 0.053-0.056 mM, respectively. Cells from the patient (T.H.)…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…The Vm. and apparent Km values were [13][14][15] nmol/h per milligram ofprotein and 0.053-0.056 mM, respectively. Cells from the patient (T.H.)…”
Section: Resultsmentioning
confidence: 94%
“…We (13,14) and others (15) reported that some patients with MSUD showed decreased amounts of E2 protein. To investigate related molecular mechanisms, we and others isolated a cDNA clone encoding the entire E2 subunit of the human BCKDH complex (16,17).…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations